Management practices and production performance of camels under organized farming in Abu Dhabi Emirate, United Arab Emirates - KUTTY, C I; YOUSUF, A M (The Indian Journal of Animal Sciences, 2017)
There is dearth of systematic studies describing the husbandry aspects and production performance of camels reared under confined farming. In this context, present study was carried out focusing 35 farm units, randomly selected from Al Wafea cluster farms, over a period of one month. Data were recorded through observation of farm activities and interview cum discussion with farm personnel and analyzed for summarizing the major findings.Different species of animals reared in the farms studied were mainly sheep and goats (90.88%), followed by camels (7.09%), cattle (1.97%) and others (0.06%). Male camels were present in most of the farms and the sex ratio was 1:13. Males above 10 years were only 13.33% indicating adequate replacement of breeding males. Types of camels were mostly Hazmi and Omani being reared in 73.33% and 66.66% of the farms respectively. Management system was semi-intensive with well-constructed houses in 80% farms, provided with a small roofed area and spacious open area. Body condition of the camels were good or fair in 93.33% farms reflecting optimum feeding and healthcare measures. However, reproductive rate was low with inter calving interval exceeding 3 years and there was 27% mortality among camel calves, which is considered one of the major drawback even in organized farming. Purpose of rearing mentioned was milk production by 93.33% of the informants. However, only 34.36% of the recently calved females were in milk with an average yield of 2.12 litres/day. Only young males were slaughtered for meat and number slaughtered in one year was only 4.45% of the total number of camels. Neither milk nor camels as such were sold as a source of income from any of the farms studied. Also there was little concern about the cost of production and is attributed to the enormous government support. Owing to sound financial position of owners, animal production is not considered a major occupation in this region. Transformation of traditional rearing into organized farming made camel production more cost oriented, but there is little effort for increasing productivity of camels or cost effectiveness of production. It is concluded that even though large number of camels are being reared under organized farming, their contribution to income and food production is very limited. However, there is considerable scope for increasing productivity of camels under organized farming utilizing the available facilities through basic level management interventions.